Fighting Smog : Energy Efficiency and Anti-Smog in Single Family Buildings in Poland - World Bank Group (World Bank, Washington, DC, 2018)
The most cost-effective way to reduce both particulate and carbon dioxide (CO2) emissions is to couple switching from noncompliant solid fuel boilers to gas boilers, heat pumps, renewable energy (RE) heating systems such as biomass, wherever possible, and compliant solid fuel boilers, as mandated in the anti-smog resolutions, with thermal retrofits of the single family building (SFB). Anti-smog resolutions and enforcement are key to create market demand for boiler replacement and fuel switching, and solid fuel quality standards are essential to reduce air pollution. For the eligible poor SFBs, the government can provide 90-100 percent of subsidies for boiler replacement, fuel switching, and thermal retrofits, channeled through municipalities. For the non-poor SFBs, the government can provide 20 percent subsidy for fuel switching to gas, heat pumps, and RE systems and thermal retrofit, together with tax incentives, channeled through commercial banks who will provide loans for the remaining investment. The anti-smog and energy efficiency are long-term efforts, and the required subsidies can be programmed over a 10-year time period. It is essential to coordinate the use of public funds from the government and European Union (EU) at both the national and regional levels, and it is recommended that a national fund for anti-smog and energy efficiency be established to pool various funding resources. Finally, technical assistance, capacity building, and public education and awareness campaigns are critical to the success of the anti-smog and energy efficiency program.